Tindak Pidana Dalam Qanun Jinayah Nanggroe Aceh Darussalam - Adinda Shalsabila Nugraha; Andromeda Mozza Hakema; Dhera Audina Mugie (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Qanun is a form of Legislation similar to Regional Regulations which regulates the procedures for administering government and community life in Aceh Province. Aceh Qanun Number 6 of 2014 concerning Jinayat Law contains prohibitions against a number of actions, and in its preamble, recognizes that the Al-Quran and Al-Hadith are the main basis of the Islamic religion which guides the people of Aceh in living a moral life based on religious teachings. The method used is a literature study technique, namely collecting various reference data from libraries, books, several journals, data sources and data analysis from journal articles, books/papers and the internet. Based on Law Number 12 of 2011, the position of Qanun Jinayah Aceh is placed in sixth place, equivalent to the Provincial Regional Regulations. This Qanun regulates various types of criminal acts in accordance with the provisions contained in Aceh Qanun No. 6 of 2014, including: Khamar, Maisir, Khalwat, Ikhtilat, Zina, Sexual harassment, Rape, Qadzaf, Musahaqah, Liwath